2024
DOI: 10.1021/jacsau.3c00802
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light-Promoted Regioselective Benzannulation of Vinyl Sulfoxonium Ylides with Ynoates

Daksh Singh Davas,
Dinesh Kumar Gopalakrishnan,
Sandeep Kumar
et al.

Abstract: Herein, we report a highly regioselective [4 + 2]-annulation of vinyl sulfoxonium ylides with ynoates under light-mediated conditions. The reaction proceeds through the new dienyl sulfoxonium ylide, which undergoes photolysis under blue light irradiation to give highly substituted naphthalene scaffolds. The method presented here operates at room temperature and does not require the addition of an external photosensitizer. The in situ-generated dienyl sulfoxonium ylide absorbs light and acts as a photosensitize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…Our study was initiated by a careful screening of reaction conditions (Scheme 1), using 4-vinylbenzamide ( 1o ) and sodium 4-chlorobenzenesulfinate ( 2 ) as model substrates, eosin Y as a photocatalyst, and nitrobenzene as a radical quencher, 27 in DMF/water under the irradiation of 3 W green light-emitting diodes (LEDs, λ max = 535 nm, I max = 1000 mA, 3.0 W; in addition to Eosin-Y, other organophotocatalysts were evaluated too, and the findings indicated that Eosin-Y was the most effective – see ESI,† general information, pages S5 and S159, for further details). We started by analysing the influence of medium acidity (entries 1–4) and rapidly observed that at a 1 : 2 ratio of eosin Y (EY) to HCl, in which EY was present in the reaction in the neutral form, the conversion was enhanced.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Our study was initiated by a careful screening of reaction conditions (Scheme 1), using 4-vinylbenzamide ( 1o ) and sodium 4-chlorobenzenesulfinate ( 2 ) as model substrates, eosin Y as a photocatalyst, and nitrobenzene as a radical quencher, 27 in DMF/water under the irradiation of 3 W green light-emitting diodes (LEDs, λ max = 535 nm, I max = 1000 mA, 3.0 W; in addition to Eosin-Y, other organophotocatalysts were evaluated too, and the findings indicated that Eosin-Y was the most effective – see ESI,† general information, pages S5 and S159, for further details). We started by analysing the influence of medium acidity (entries 1–4) and rapidly observed that at a 1 : 2 ratio of eosin Y (EY) to HCl, in which EY was present in the reaction in the neutral form, the conversion was enhanced.…”
mentioning
confidence: 99%
“…In the absence of Eosin Y, the reaction proceeded with a 21% conversion rate, which was likely the result of oxygen-driven photochemistry (entry 21). 27 Despite being conducted in complete darkness, the reaction could still occur. It was postulated to have commenced shortly after the reaction was established before being placed in a dark compartment (entry 22).…”
mentioning
confidence: 99%
See 1 more Smart Citation